A 1286‐year hydro‐climate reconstruction for the Balkan Peninsula. (3rd May 2018) - Klippel, Lara; Krusic, Paul J.; Brandes, Robert; Hartl, Claudia; Belmecheri, Soumaya; Dienst, Manuel; Esper, Jan
Abstract : We present a June–July drought reconstruction based on the standardized precipitation index (SPI) for the Balkan Peninsula over the period 730–2015 CE. The reconstruction is developed using a composite Pinus heldreichii tree‐ring width chronology, from a high‐elevation network of eight sites in the Pindus Mountains in northwest Greece, composed of living trees and relict wood. The dataset includes the ring width series of Europe's currently oldest known living tree, dendrochronologically dated to be more than 1075 years old. The spatial coverage of the reconstruction is improved by using an averaged gridded SPI data target derived from a response field that is located north of the study region. Justification for this approach includes the remoteness of instrumental data, the spatial variability of precipitation and synoptic scale circulation patterns. Over the past 1286 years, there have been 51 dry and 43 pluvial events. The driest year during the 1286‐year‐long period was 1660 and the wettest year was 1482. Comparison with shorter reconstructions and documentary evidence validates the new reconstruction, and provides additional insight into socioeconomic impacts and spatial patterns of extreme events. Fifty‐nine of 72 previously undescribed extremes occurred prior to the 17th century. The new reconstruction reveals long‐term changes in the number of extremes, including substantially fewer drought and pluvial events in the 20th century. Additional tests on the long‐term effects of age structure, replication and covariance changes support the heteroscedastic nature of the reconstructed hydro‐climatic extremes.